PENGARUH MOTIVASI KERJA DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT RADIO PERMATA SWARANUSA - Hanif, Fauzan; Muttaqiyathun, Ani (Universitas Ahmad Dahlan, 2013)
This study aims to analyze the influence of work motivation and remuneration of the employeeâ€™s performance in PT Radio Permata Swaranusa. The sample of Â the research are all employees of PT Radio Swaranusa which amount 30 people who more throughout the field of PT Radio Permata Swaranusa. The usage of analytical method is a statistical method by using a multiple linear regression analysis and t-test. The result of the analysis which has been done, generate that is significantly more influenced motivation 0.016 (Sig.) < 0.05 (alpha) and sompensation 0.831 (Sig.) > 0.05 (alpha).